Partial purification and characterization of alkaline proteases from maize (oba super 2) - AGBO, Anthony Ogbonnia; ODIBO, Fredrick Chidi Jeramiah (Bangladesh Journal of Scientific and Industrial Research, 2025)
Proteases are enzymes that degrade proteins into their constituents amino acids and peptide bonds. Despite the availability of plants, their proteases are the least utilized. This study examined the purification and characterization of two different alkaline proteases from Oba Super 2 maize. Standard procedures were used to prepare certified samples, extract and purify enzymes. A substrate casein was used for characterization, and the proteases were identified as alkaline serine proteases (1) and (11) by native polyacrylamide gel electrophoresis, with molecular masses of 62.81 and 63.44 kDa, respectively. The proteases were most active and stable at 50 and 600C, pH 9 and 8, were activated by Cu2+ and dimethyl sulfoxide, while phenylmethylsulphonyl fluoride was the potent inhibitor. In the presence of some surfactants, oxidants, and detergent (ariel), the proteases remained stable. These proteases showed promising qualities for utilization in relevant sectors. Bangladesh J. Sci. Ind. Res. 60(1), 9-24, 2024